The meaning of life according to patients with advanced lung cancer: a qualitative study - Jin Mei Zhang; Mei Rong Zhang; Chun Hong Yang; Yumei Li (International Journal of Qualitative Studies on Health & Well-Being, 2022)
Purpose This qualitative study explores the meaning of life and end-of-life coping strategies among patients in China with advanced lung cancer. Methods We conducted in-depth interviews with 21 hospitalized patients with advanced lung cancer and analysed the data using the 7-step Colaizzi method. Results The analysis revealed themes in patients’ experiences and feelings about living with a terminal illness. These include: 1) The core of the meaning of life is “self-iteration,” which includes self-recognition and cherishing life; 2) The existence form of the meaning of life is “yu-wei,” including self-reliance and altruism; 3) The meaning of life is embodied in three levels: the past, present, and future. The past includes gratitude, guilt and remorse, and avoidance; the present includes using the support system, positive response, independence, and integrity; the future includes accompanying relatives, preparing for death, living a high quality of life, and worrying. Conclusion Meaning of life is a multidimensional and diverse concept among patients with advanced lung cancer. Medical care providers and family members can provide targeted professional guidance and psychological support according to patients’ characteristics to help them discover their meaning of life, improve their quality of life, and achieve a positive end-of-life perspective.